Implementation of Inclusive Education from the Perspective of School Management in Primary Schools - Hasanah, Nisa Kartika; Sunardi, Sunardi; Yuwono, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
This study aims to analyze the implementation of inclusive education in elementary schools in Purworejo Regency from the perspective of school management. The research employed a quantitative approach using a questionnaire as the instrument. Validity testing, reliability testing, descriptive analysis, normality testing, and correlation testing were conducted to analyze the data. The findings indicate that all instruments were valid and reliable. Descriptively, the curriculum and student affairs aspects achieved relatively high performance, while the HR, facilities and infrastructure, community participation, and financing aspects remained low. Correlation analysis revealed that all seven management aspects were significantly associated with the effectiveness of inclusive education implementation (p < 0.05). The strongest relationships were found in community participation (r = 0.939) and HR (r = 0.936). The study also shows that most schools have gradually attempted to implement management functions, although challenges remain in teacher training, limited facilities and infrastructure, and support from policymakers. Nevertheless, principal initiatives, teacher collaboration, and parental involvement serve as key supporting factors in sustaining inclusive education implementation.